Formigas epigéicas em resposta a um gradiente sucessional em fragmentos de caatinga no alto sertão sergipano - Oliveira, Anny Carolyne Ferreira de (2012)
The Caatinga is going through a process of accelerated modification resulting from the inappropriate use of their natural resources. These modifications end up provoking a number of changes in the dynamics of the communities and becoming one of the factors that may affect directly or indirectly the richness and composition of myrmecofauna. This work has been verified as heterogeneity (wealth of trees), complexity (density of trees) and environmental soil nutrients concentration influence in the richness of ant s epigaeic into three fragments of the Caatinga. The collections occurred in four steps distributed throughout the year (February, may, July, November) by 2011, in three areas of the Caatinga located in Alto Sertão Sergipano. Early - area used as pasture; Intermediate - area in the natural regeneration process of 4 years; Late - fragment of the Caatinga well-preserved with a presence of tree large species. The myrmecofauna collection have been delineated five plots (20 m x 50 m) in each area, in which 10 were installed type Pitfall traps of drop baits containing sardines, respecting a minimum distance of 10 m between them, totaling 50 traps/stage. The traps remained were exposed for a period of 48 hours. Also were collected 46,616 at specimens, distributed in six subfamilies and 44 morpfospecies. Through the analysis of multidimensional scale non-metric (NMDS), parcels of late stage were isolated from other areas, initially and intermediary, showing that there is a change in the composition of species of ants as they progress through the successional stage. The wealth of epigaeic ants ranged between the successional stages (F = 11.78; p = 0.0003), being that the portions of the late stage have a greater wealth of average compared to other ants. On one hand, a significant difference was observed between the successional gradients and soil nutrients, with emphasis on the intermediate stage, which presented the largest concentrations of (Na, K, P, CTC, Ca and Mg) compared to the other stages. On the other hand, there was no significant difference when assessing the influence of soil nutrients under the richness and composition of epigéicas ants. Wealth and plant density may represent increased resources available such as nesting sites and food sources, contributing to the increase in species richness of ants during the process of forest succession.